Investigating the diagnostic accuracy of vertebral heart score, vertebral left atrium score and thoracic width measurement in cats with suspected cardiac problems - B. Ozdil; T. M. Parlak; M. Arican (Bulgarian Journal of Veterinary Medicine)
This study aimed to evaluate vertebral heart score (VHS) in terms of sensitivity and accuracy of ra-diographic heart examination for early diagnosis of cardiac diseases in cats and to compare vertebral left atrium score (VLAS), N-terminal pro-B-type natriuretic peptide (Nt-proBNP) with thoracic width measurement (TWM). Thirty cats were used. Ten of these cases were used as the control group. The remaining 20 cases formed the group with suspected heart problems. The VHS, VLAS and thoracic width were measured by radiographic examination. Blood was drawn and Nt-proBNP concentrations were assayed in all animals. As a result, VHS was above the reference range in 14 cases. For VLAS measurements, 7 cases had values above the reference range. TDM was above the normal reference range in 5 cases from the control group. There was no statistically significant correlation between VHS and VLAS (P=0.07), VHS and TWM (P=0.06), VHS and Nt-proBNP (P=0.05). However, in cases with high VHS, VLAS, TWM, and Nt-proBNP values, elevated levels were observed in 50% of the cases compared to the reference values. However, radiographically measured VHS, VLAS, and TWM may represent independent measurements. No statistically significant relationship was found between them. It would be beneficial to conduct mroe extensive studies by considering the breed, age and weight in cats with suspected heart problems.